All‐in‐One DNA Extraction Tube for Facilitated Real‐Time Detection of Infectious Pathogens. Issue 14 (29th May 2021) - Song, Younseong; Kim, Yong Tae; Choi, Yunho; Kim, Hogi; Yeom, Min Hee; Kim, Yesol; Lee, Tae Jae; Lee, Kyoung G.; Im, Sung Gap
Abstract: An "all‐in‐one tube" platform is developed, where the genetic analysis involving DNA extraction, amplification, and detection can be performed in a single tube. The all‐in‐one tube consists of a polymerase chain reaction (PCR) tube in which the inner surface is conformally modified with a tertiary‐amine‐containing polymer to generate a strong electrostatic interaction with DNA. The all‐in‐one tube provides high DNA capture efficiency exceeding 80% from Escherichia coli O157: H7 pathogen at a wide range of DNA amount from 0.003 to 3 ng. Indeed, the use of the surface‐functionalized PCR tube enables direct amplification and detection of the surface‐captured DNA without the modification of standard real‐time PCR instrument. Besides, this platform has sensitivity, selectivity, and reliability enough for accurate detection at the minimal infective dose of both gram‐positive and negative pathogens. The all‐in‐one tube enables the direct molecular diagnosis, substantially reducing the labor‐intensive pathogen detection steps while providing high compatibility with the currently established real‐time PCR instruments, and illustrates its on‐site applicability with convenience expandable to various genetic analyses including food safety testing, forensic analysis, and clinical diagnosis. Abstract : An all‐in‐one tube is devised by coating poly‐(2‐dimethylaminomethyl styrene) on a polymerase chain reaction (PCR) tube via initiated chemical vapor deposition to extract, amplify, and detect pathogens within a single tube. The all‐in‐one tube can capture DNA by charge interaction and directly perform real‐time PCR. The all‐in‐one tube can also detect four pathogens from artificially infected food samples.